2007
DOI: 10.1038/ni1478
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-6 mediates the germinal center B cell phenotype and lymphomagenesis through transcriptional repression of the DNA-damage sensor ATR

Abstract: Antibody specificity and diversity is generated in B cells during germinal center maturation through clonal expansion while they undergo class-switch recombination and somatic hypermutation. Here we demonstrate that the transcriptional repressor Bcl-6 mediates this phenotype by directly repressing ATR in centroblasts and lymphoma cells. ATR is critical in replication and DNA damage-sensing checkpoints. Bcl-6 allowed B cells to evade ATR-mediated checkpoints and attenuated the response of the B cells to exogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
283
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 242 publications
(294 citation statements)
references
References 51 publications
10
283
0
1
Order By: Relevance
“…Recent work revealed that Bcl6 is also needed for follicular T helper cell development [10][11][12]. Analyses of Bcl6 target genes in B cells indicate that suppression of apoptosis and cell cycle arrest responses occur through p53, p21 and CHEK1 and Bcl6 also regulates DNA damage responses by controlling ATR [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Recent work revealed that Bcl6 is also needed for follicular T helper cell development [10][11][12]. Analyses of Bcl6 target genes in B cells indicate that suppression of apoptosis and cell cycle arrest responses occur through p53, p21 and CHEK1 and Bcl6 also regulates DNA damage responses by controlling ATR [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Structural studies revealed that SMRT, NCoR, and BCoR all bind to a lateral groove in the POZ domain through a stretch of 17 amino acids (1). Using a cell-permeable BCL6 peptide inhibitor, BPI, designed to block POZ lateral groove corepressor recruitment, we have shown that SMRT/NCoR/BCoR control cell proliferation and survival in GC-derived B cells by mediating BCL6-dependent repression of genes such as ATR, TP53, and CDKN1A (32,35,37). The RDII corepressors, HDAC2 and MTA3/NuRD, bind to BCL6 in an acetylation-sensitive manner and are dissociated from BCL6 when the KKYK motif within RDII is acetylated (4, 15).…”
mentioning
confidence: 99%
“…GC are dynamic and specialized structures in the secondary lymphoid organs within which B cells undergo immunoglobulin class switch recombination and somatic hypermutation to produce diverse, high-affinity antibodies (17,26). Widely considered to be the master regulator of the GC stage of B-cell development, BCL6 maintains the GC-specific gene expression program by silencing genes involved in B-cell activation (CD69, CD80, and NF-B1), response to DNA damage (TP53 and ATR), cell-cycle regulation (CCND2, CDKN1B, and CDKN1A), and plasma cell differentiation (PRDM1) (25,29,34,37,38,40,41). Thus, neither the memory nor the plasma cell differentiation program can be initiated until expression and activity of BCL6 are extinguished by GC exit signals.…”
mentioning
confidence: 99%
“…One of the best characterized biological functions of BCL6 in centroblasts is to facilitate simultaneous rapid proliferation and tolerance of genomic damage occurring during clonal expansion and somatic hypermutation. BCL6 mediates these effects by directly repressing DNA damage sensing and checkpoint genes such as DNA damage sensor ATR (ataxia telangiectasia and Rad3 related), TP53 (tumor protein p53) tumor suppressor and cell cycle arrest gene CDKN1A (cyclin-dependent kinase inhibitor 1A) [27][28][29]. In addition, BCL6 blocks premature activation by T cells or other soluble signals through inhibiting a number of pathways involved in B-cell activation in T-cell dependent immune [11][12][13].…”
Section: Bcl6: a Master Transcriptional Regulator Of Gc B-cell Develomentioning
confidence: 99%